Self-Regulation and Grit: The Role of Self-Regulation and Grit in Overcoming Thesis Writing Anxiety among Final-Year Students - Oktavia, Anisa; Viranda, Chintia (Psikostudia : Jurnal Psikologi, 2024)
A thesis is a mandatory component for every student to achieve an academic degree. Final year students engaged in conducting their theses sometimes experience heightened levels of anxiousness. Hence, interventions are necessary to mitigate this concern. One approach is to enhance self-regulation and grit abilities in the individual. This study aims to evaluate the effect of self-regulation and grit on anxiety levels experienced by final year students as they prepare to write their theses. Using a quantitative research strategy, our study zeroed down on 252 seniors working on their capstone projects. The approach used for participant selection was Probability Sampling with Purposive Random Sampling. The data for this study was collected using three questionnaire scales: the self-regulation scale with 21 items, the grit scale with 9 items, and the anxiety scale with 33 items. Simultaneously, the employed data analysis methods for hypothesis testing include simple linear regression analysis and multiple linear regression analysis. The findings of the study indicate that both self-regulation and grit exert a detrimental impact on anxiety. Specifically, self-regulation is found to have a negative influence on anxiety, whereas grit is positively associated with anxiety.Penulisan skripsi adalah prasyarat penting bagi mahasiswa untuk meraih gelar akademik. Proses ini seringkali menimbulkan kecemasan di kalangan mahasiswa tingkat akhir yang sedang dalam proses penyelesaian skripsi. Maka dari itu, diperlukan upaya untuk mencegah rasa cemas tersebut, salah satunya dengan upaya meningkatkan kemampuan regulasi diri dan grit pada individu tersebut. Penelitian ini bertujuan untuk menentukan dampak regulasi diri dan ketangguhan, juga dikenal sebagai grit, terhadap tingkat kecemasan mahasiswa tingkat akhir selama proses penyusunan skripsi. Dalam penelitian ini, metode kuantitatif dipilih. Sebanyak 252 mahasiswa tingkat akhir yang mengerjakan skripsi diambil dengan teknik purposive sampling probabilitas.Data dalam penelitian ini dikumpulkan menggunakan tiga skala kuesioner: skala regulasi diri dengan 21 item, skala grit yang memiliki 9 item, dan skala kecemasan yang berisi 33 item. Analisis regresi linear sederhana dan berganda adalah dua teknik analisis data yang digunakan untuk menguji hipotesis. Hasil dari penelitian menunjukkan regulasi diri dan grit berpengaruh yang bernilai negatif terhadap kecemasan, regulasi diri berpengaruh yang bernilai negatif terhadap kecemasan, dan grit berpengaruh yang bernilai negatif terhadap kecemasan.